2023
DOI: 10.1111/jch.14714
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric sarcopenia is associated with hypertension: A systematic review and meta‐analysis

Yawen Quan,
Chang Wang,
Linfeng Wang
et al.

Abstract: This meta‐analysis aimed to explore the potential relationship between senile sarcopenia and hypertension in older people. A comprehensive search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library, up to November 2022. Ten studies comprising 14 804 participants were enrolled. The odds ratio (OR) and 95% confidence interval (CI) was pooled to evaluate the correlation between sarcopenia and hypertension in older people utilizing a random‐effects model. Subgroup and sensitivity analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Sarcopenia and hypertension are strongly and independently associated with CVD, indicating the importance of controlling both conditions. 3,4 Nutrition and exercise are the cornerstones of sarcopenia management, but BP control may be difficult in this vulnerable population at risk for adverse events. 2 While past studies have shown the benefits of aggressive hypertension treatment The outcomes included cardiovascular disease events (A), all-cause mortality (B), and serious adverse events (C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia and hypertension are strongly and independently associated with CVD, indicating the importance of controlling both conditions. 3,4 Nutrition and exercise are the cornerstones of sarcopenia management, but BP control may be difficult in this vulnerable population at risk for adverse events. 2 While past studies have shown the benefits of aggressive hypertension treatment The outcomes included cardiovascular disease events (A), all-cause mortality (B), and serious adverse events (C).…”
Section: Discussionmentioning
confidence: 99%
“…DOI: 10.1161/HYPERTENSIONAHA.124.23011 is consistently linked with increased rates of hypertension and CVD. [2][3][4][5] Thus, the challenge lies in reconciling recommendations for intense BP management with the increased vulnerability of older individuals who have both sarcopenia and hypertension. 6,7 This necessitates a finely calibrated approach to managing hypertension for these patients, carefully balancing effective treatment against the risk of potential adverse events.…”
Section: Original Article E78 August 2024mentioning
confidence: 99%
“…Sarcopenia has been related to numerous adverse outcomes, including poor health-related quality of life, cognitive decline or hypertension and cardio-cerebrovascular disease or even increased mortality [ 12 , 13 , 14 , 15 , 16 , 17 ]. Moreover, sarcopenia has been associated with higher intensive care unit admission and increased hospital stays, severity of disease and risk of mortality among COVID-19 patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%